Growth of HIV-Exposed Infants in Southwest China: A Comparative Study - Ji-Chang Chen MD; Yu Zhang PhD; Chokechai Rongkavilit MD; Bo Wang PhD; Xue-Mei Huang MD; Zheng Nong MD; Jing Liu MD; Dingyuan Zeng PhD; Eric McGrath MD (Global Pediatric Health, 2019)
Objectives . Prevention of mother-to-child HIV transmission has been globally successful leading to a decline in HIV-infected infants. Thus, the number of HIV-exposed, but uninfected, infants is increasing. As growth is an important indicator of child health, this study aimed to evaluate growth parameters of HIV-exposed Chinese infants. Methods . A prospective study was conducted among HIV-exposed (HIV-infected and uninfected) infants born during 2007 to 2015 in Liuzhou, China. Their weight and length were assessed longitudinally from birth to 18 months of age and compared with HIV-unexposed, uninfected (HUU) infants from the same region. Results . There were 467 HIV-exposed infants. Four percent of infants were HIV-infected. The mean weight-for-age (WAZ) and length-for-age (LAZ) z scores of HIV-infected infants were significantly lower than those of HIV-exposed but uninfected (HEU) infants during 9 to 18 months and 12 to 18 months of age, respectively. Additionally, the mean WAZ and LAZ scores of HIV-infected infants were significantly lower than HUU infants during the first 12 months and 18 months of life, respectively. The mean WAZ and LAZ scores of HEU infants were significantly lower than HUU infants during the first 12 months and 6 months of life, respectively. HEU infants also had a lower mean weight-for-length z score than HUU infants during the first 6 months. Conclusion . We demonstrated poor growth among HIV-exposed Chinese infants, including HIV-uninfected, compared with HUU infants. The results emphasize the need for nutritional monitoring and interventions for HIV-exposed infants regardless of HIV infection status. Research is needed on long-term growth trajectories and factors affecting growth of HIV-exposed infants in China.